(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
The actuality of this article lies on the implementation of the latest reforms in the system of education, particularly in teaching foreign languages and preparing competent language teachers for every branch of education. Writing this article also will be my contribution to the development of science and innovative technologies.